The Reputation Driven Interplay of Relationships between Clients and Auditors in an Auditor Selection Process: A Multilevel Network Approach - Slobodan Kacanski (Journal of Accounting and Management Information Systems (JAMIS), 2017)
This study investigates the reputation-based interplay between auditor selection and interlocking directorships from a multilevel network perspective. The aim of this article is to explore how and under what conditions reputation influences patterns of social selection processes in an assurance service context. To empirically determine the impact of reputation on establishing relational ties, this study applies exponential random graph models (ERGMs) for multilevel networks. The case study was carried out in the Danish field of mandatory audits, and findings here make a valuable contribution to the literature on auditor selection. A total of 774 annual reports were collected from 145 - 165 Danish public listed companies, and the relational data of companies was assembled, as comprised of the members of supervisory boards and partners who signed audit reports during the five-year period from 2010 to 2014. In this study, mechanisms for auditor selection were controlled by mechanisms for interlocking directorships in order to obtain a broader picture of the conditions under which board members have tendencies to select reputable auditors. The findings suggest that reputation has a significant impact on both observed processes, however, results reveal that reputation has a compensatory nature, as it drives both mechanisms of social selection but never simultaneously.
Keywords: M42; 650; reputation; board of directors; interlock directorship; network; ERGMs